Immunoelectron microscopic characterization of glial intermediate filaments in human gliomas - Geiger, Dietrich Horst (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MMed (Biomedical Sciences. Anatomy and Histology))--University of Stellenbosch, 1993.